INFLUENCE OF DIETARY MORINGA OLEIFERA LEAF EXTRACT ON GROWTH PERFORMANCE, BLOOD PROFILE AND IMMUNE STATUS OF AFRICAN CATFISH (CLARIAS GARIEPINUS): Performance of African catfish on moringa leaf extract - Adeniyi, O. V.; Setufe, S. B.; Ajao, H. A.; Shabako, G. M. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
This study investigated the effects of Moringa oleifera leaf (MOL) extract on the performance and immune response of Clarias gariepinus challenged with Aeromonas hydrophila. Five diets containing 0 (positive control), 0.5, 1.0 or 2.0g MOL extract and 0.5g synthetic (negative control) / kg basal diets were formulated and fish were fed the formulated diets to apparent satiation twice daily for 56 days. Thereafter, fish were challenged with A. hydrophila through intraperitoneal injection. Blood samples were collected from the experimental fish before and after fish challenge for analyses of haematological, and biochemical parameters. The data obtained were analyzed using one-way analysis of variance at P < 0.05. Fish fed with 2.0 MOL g/kg diet had significantly higher weight gain, specific growth rate, and lower feed conversion ratio, compared to those fed the 2 control and other MOL-fortified diets. The red blood cell, white blood cell and lymphocyte counts were boosted significantly with increasing levels of MOL extract in the diet. The albumin in fish fed MOL-fortified and synthetic-based diets were significantly higher than the fish fed positive control diet, while alanine aminotransferase and aspartate aminotransferase reduced in fish fed MOL-based diets. The fish fed diets fortified with 1.0 and 2.0g MOL showed enhanced respiratory burst, phagocytic activities and post-challenge survival than those fed the control diets. In conclusion, dietary MOL extract at 2.0g/kg inclusion significantly enhanced growth performance, the physiological status, and protection against A. hydrophila infection in C. gariepinus and hence the concentration is recommended for its production. Keywords: Blood profile, Clarias gariepinus, growth performance, immune response, Moringa oleifera extract.